2018
DOI: 10.1111/jgh.14508
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of adding oral simethicone in bowel preparation regimen for the detection of colon adenoma: A systematic review and meta‐analysis

Abstract: Background and Aim Simethicone is an anti‐foaming agent commonly used during colonoscopy. Although several randomized trials have shown that oral simethicone in the bowel preparation regimen may improve bowel cleanness, whether it improves adenoma detection rate (ADR) or polyp detection rate remains undetermined. The aim of this study was to determine if oral simethicone in bowel preparation regimen before colonoscopy improves the ADR. Methods A comprehensive literature review was conducted using PubMed, SDOL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Simethicone (SIM) is an antifoaming agent, which helps reduce the formation of bubbles and improve bowel visibility; therefore, it is recommended as an important adjunct for bowel preparation prior to colonoscopy . Moreover, most studies have shown that use of SIM can help improve bowel preparation efficacy, shorten the cecal intubation time and increase the ADR . In a few studies, use of SIM did not help improve the ADR or reduce the procedure time; however, it is still recommended for bowel preparation as it reduces the need for intraprocedural use of SIM and decreases the risk of endoscope‐transmitted infection …”
Section: Introductionmentioning
confidence: 99%
“…Simethicone (SIM) is an antifoaming agent, which helps reduce the formation of bubbles and improve bowel visibility; therefore, it is recommended as an important adjunct for bowel preparation prior to colonoscopy . Moreover, most studies have shown that use of SIM can help improve bowel preparation efficacy, shorten the cecal intubation time and increase the ADR . In a few studies, use of SIM did not help improve the ADR or reduce the procedure time; however, it is still recommended for bowel preparation as it reduces the need for intraprocedural use of SIM and decreases the risk of endoscope‐transmitted infection …”
Section: Introductionmentioning
confidence: 99%
“…The presence of luminal bubble in colonoscopy may affect the ADR and AADR [13]. The routine use of simethicone during endoscopy procedure is not well established in China due to the lack of awareness of such practice.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other studies have evaluated the effect of simethicone on adenoma detection with varying bowel preparations. A meta-analysis by Yeh et al[27] evaluated 12 randomized controlled trials with a total number of 6003 patients and concluded no significant difference in ADR when simethicone was used, although sub group analysis revealed a difference in populations with low baseline ADRs. On the contrary, meta-analysis performed by Pan et al[28] showed supplemental simethicone improved ADR for colonoscopy.…”
Section: Discussionmentioning
confidence: 99%